From Musaylima to the KhÄrijite Najdiyya - Makin, Al (Al-Jamiah: Journal of Islamic Studies, 2013)
This paper tries to reconstruct the following accounts: the defeat of Musaylima and the death of his prominent followers, and the rise of the KhÄrijite Najdiyya in Yamama. Moreover, this study seeks the evidence which points to the possible connection between Musaylimaâs movement and the KhÄrijite Najdiyya. This paper highlights that many founders and prominent leaders of the KhÄrijites, and particularly the Najdiyya sect, came from the tribe of á¸¤anÄ«fa, to which Musaylima belonged. This, among other things, seems to have become the main impulse of attraction for the people of á¸¤anÄ«fa to join the sect. Additionally, the âcharacteristicsâ and the âimageâ of the Najdiyya reflect those of Musaylima. This leads us to conjecture that the people of á¸¤anÄ«fa, having failed to defend their prophet Musaylima and the land of YamÄma against the Medinan caliphate under AbÅ« Bakr in the Battle of âAqraba, later joined the KhÄrijite Najdiyya. [Artikel ini menjelaskan kekalahan Musaylima dan kematian pengikut-pengikut utamanya serta kemunculan aliran KhawÄrij Najdiyya di YamÄma. Melalui artikel ini, penulis membuktikan relasi antara gerakan Musaylima dan KhawÄrij Najdiyya. Ini bisa dibuktikan dengan mencermati fakta bahwa sebagian pendiri dan tokoh utama KhawÄrij, utamanya sekte Najdiyya, berasal dari suku á¸¤anÄ«fa suku yang juga menjadi asal muasal Musaylima. Kesamaan suku inilah dan beberapa faktor lainnya nampaknya menjadi daya tarik tersendiri bagi orang-orang suku á¸¤anÄ«fa untuk bergabung dengan sekte Najdiyya. Selain itu, âkarakteristikâ dan âimejâ sekte Najdiyya yang menyerupai gerakan Musaylima adalah hal lain yang turut menguatkan asumsi tersebut. Pandangan inilah yang kemudian mengantarkan penulis pada kesimpulan bahwa setelah gagal mempertahankan nabi mereka, Musaylima, dan wilayah mereka, YamÄma, melawan khilafah Islam di Madinah yang dipimpin AbÅ« Bakr, suku á¸¤anÄ«fa memilih memberontak dan bergabung dengan sekte KhawÄrij Najdiyya.]